A influência de atividades agrícolas sobre a vegetação remanescente de cerrado em assentamentos rurais no estado de Goiás - Gosch, Marcelo Scolari (2015)
This research has focused on the land use dynamic in the settlement land projects located in the state of Goiás with the predominance of intensive agriculture (commodities), family agriculture and extensive livestock. The main objective is to analyze the influence and the impacts of different agriculture activities developed regionally over the remaining native vegetation in the Settlement Projects. Our hypothesis is that different forms of occupation and economic exploitation in the Cerrado have different impacts on the legal reserve vegetation found in the rural settlements. Thus we attempted to understand the environmental condition of the rural settlements in its micro region, analyze the evolution of deforestation within the settlements and their surroundings, trying to understand the relationship of the developed agricultural activities with the rural settlements patterns. Our methodology adopted the use of GIS techniques, satellite image classification (Landsat-TM 5 and RapidEye imageries), besides the use of geo-referenced data and visiting fieldwork at the settlement samples. The results indicated that, although the rural settlements have a higher rate of deforestation (between 1990 – 2010 period), the percentage cleared inside them was less than their surroundings. This result shows that regions with more intensive land use (with agriculture or pastures) tend to suffer with a higher pressure of the deforestation, both regionally and within the settlements. Therefore, the settlements tend to follow the regional dynamics of deforestation or conservation actions of the area where they are installed, bring the same agricultural activities of their surroundings. We conclude that the settlements from rural reform agrarian in the Cerrado biome are not isolated lands from the local reality, while their small farmers settled can not be characterized as the main actors of the land use changes in Goiás state.